Aksjologiczny wymiar Konstytucji Rzeczypospolitej Polskiej - Malinowska, Ewa (Stylistyka, 2019)
This paper is an attempt to show the axiological dimension of the currently binding basic law, i.e. the Constitution of the Republic of Poland of 1997. The text of the constitution is a carrier of the values important to Poles, and it is predisposed to this by its specific content, a superior position in the hierarchy of normative acts and a high social authority. The information about the most important values is already provided by the constitutional introduction (preamble) – it includes the most important values of the entire community of the state expressis verbis. In terms of values, the author tries to read and interpret the general principles of the constitution (the constitutional principles of law) and the chapter on the freedoms and rights of persons and citizens. The basic principles of the Constitution of the Republic of Poland are: the principle of a democratic state ruled by law and the tripartite separation of powers, and the priority value is man, his freedom and dignity, as well as the common good of all citizens. These values result from the adopted concept of a democratic state of law.